2016
DOI: 10.1093/jxb/erw019
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing cytokinin synthesis by overexpressingiptalleviated drought inhibition of root growth through activating ROS-scavenging systems inAgrostis stolonifera

Abstract: HighlightThe relationship between an adenine isopentenyltransferase transgene, reactive oxygen species (ROS) content and the ROS-scavenging system, mechanistically contributing to improved root growth under drought stress in creeping bentgrass, is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 137 publications
(86 citation statements)
references
References 75 publications
5
74
0
1
Order By: Relevance
“…Kentucky bluegrass, in contrast, showed no significant effect of drought stress on leaf superoxide dismutase activity (Zhang & Schmidt, ). Da Costa and Huang () reported a consistent decrease in both superoxide dismutase and catalase activities in the leaves of creeping bentgrass when exposed to prolonged water‐deficit, and similar decreases in superoxide dismutase expression were reported in the roots of drought‐stressed creeping bentgrass (Xu et al., ). Root catalase activity was substantially higher and peroxidase activity was decreased, while glutathione and total ascorbate content remained unaffected (Xu et al., ).…”
Section: Effects Of Drought On Metabolism Of Cool‐season Grassessupporting
confidence: 58%
See 2 more Smart Citations
“…Kentucky bluegrass, in contrast, showed no significant effect of drought stress on leaf superoxide dismutase activity (Zhang & Schmidt, ). Da Costa and Huang () reported a consistent decrease in both superoxide dismutase and catalase activities in the leaves of creeping bentgrass when exposed to prolonged water‐deficit, and similar decreases in superoxide dismutase expression were reported in the roots of drought‐stressed creeping bentgrass (Xu et al., ). Root catalase activity was substantially higher and peroxidase activity was decreased, while glutathione and total ascorbate content remained unaffected (Xu et al., ).…”
Section: Effects Of Drought On Metabolism Of Cool‐season Grassessupporting
confidence: 58%
“…Increases in membrane damage are often observed in drought‐stressed plants, and significant increases in electrolyte leakage have been reported in cool‐season grasses, including creeping bentgrass (Burgess & Huang, ,b; Merewitz, Gianfagna, & Huang, ; Xu, Burgess, Zhang, & Huang, ), tall fescue (Huang & Gao, ; Yu, Chen, et al., ), perennial ryegrass (AbdElgawad, Farfan‐Vignolo, et al., ; Farfan‐Vignolo & Asard, ), and Kentucky bluegrass (Abraham, Meyer, Bonos, & Huang, ; Jiang & Huang, 2001b; Yang, Xu, Yu, DaCosta, & Huang, ). However, Yu, Chen, et al.…”
Section: Effects Of Drought Stress On Cool‐season Grass Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Under stressed conditions cytokinins progress cell division and elongation so that younger leaves could carry on as sink. Diminished cytokinins production by the roots is associated with drought stress, which can possibly hasten senescence in the older leaves by hindering its generation (Xu et al, 2016). Acid invertase is assumed to be an imperative part in the carbohydrate metabolism, which is definitely recognized with the remobilization of storage reserves from leaves or stems (Zinselmeier et al, 2000), its action is likewise impeded by drought stress (Zinselmeier et al, 1995).…”
Section: Effect Of Drought On Plant Developmental Processesmentioning
confidence: 99%
“…ROS generation is considered to be closely related to lipid peroxidation under drought stress (Ryan et al., ; Uzilday et al., ). For example, lipid peroxidation analysis showed that transgenic Agrostis stolonifera L. root exhibited less cellular damage when compared with the wild type under drought stress conditions (Xu et al., ). The alleviation of adverse effects of drought stress is partially attributable to an increased antioxidant ability and decreased lipid peroxidation induced by early ROS accumulation (Xing et al., ).…”
Section: Discussionmentioning
confidence: 99%